Pengaruh Model Teams Games Tournament (TGT) Berbantuan Flashcard terhadap Kemampuan Membaca Permulaan Peserta Didik Kelas II di SDN 31 Ampenan - Olevia Siptiandari; Sukri; Hasnawati (Mataram University, 2026)
Early reading is a basic skill that is important to be mastered by elementary school students as a foundation in acquiring various learning competencies. This study aims to determine the effect of the flashcard-assisted teams games tournament (TGT) model on the early reading skills of second-grade students at SDN 31 Ampenan. This study is a quantitative study with a quasi-experimental design with a nonequivalent control group design. The subjects of the study were second-grade students at SDN 31 Ampenan. The data collection method used observation and a beginning reading skills test that had been tested for validity. The results of the study showed a significant difference in the beginning reading skills of the two classes, so Ho was rejected and Ha was accepted. Finally, the results of the N-Gain test showed that the increase in the beginning reading skills of students in the experimental class was higher than in the control class. Based on the results of the study, it can be concluded that there is an effect of the flashcard-assisted TGT model on the beginning reading skills of second-grade students at SDN 31 Ampenan.